Connotative Meaning in “Do Not Stand at My Grave and Weep” Poem by Mary Elizabeth Frye - Syazwina, Alika; Sitompul, Jui Fasco Rini; Fitriyah, Fitriyah (Modality Journal: International Journal of Linguistics and Literature, 2024)
Connotative meaning refers to the additional meanings associated with a word beyond its literal definition, often carrying positive or negative values. This research aims to analyze the connotative, or hidden, meanings in the poem “Do Not Stand at My Grave and Weep” by Mary Elizabeth Frye. The study employs a qualitative research method to analyze the data. It utilizes Leech's theory to explore the connotative meanings within the poem. Each phrase and couplet in “Do Not Stand at My Grave and Weep” was categorized based on its connotative meaning, and the specific aspects of each connotative word were identified. Following the analysis, the researchers provided explanations for the data and drew conclusions based on their findings. As a result, 12 distinct connotative meanings were discovered in this poem. In conclusion, connotative meaning differs from literal meaning found in a dictionary, and it can sometimes be more challenging to decipher the hidden significance behind it. AbstrakMakna konotatif merujuk pada makna tambahan yang dikaitkan dengan sebuah kata di luar definisi literalnya, yang sering kali membawa nilai positif atau negatif. Penelitian ini bertujuan untuk menganalisis makna konotatif, atau makna tersembunyi, dalam puisi "Do Not Stand at My Grave and Weep" oleh Mary Elizabeth Frye. Penelitian ini menggunakan metode penelitian kualitatif untuk menganalisis data. Penelitian ini memanfaatkan teori Leech untuk mengeksplorasi makna konotatif dalam puisi tersebut. Setiap frasa dan bait dalam "Do Not Stand at My Grave and Weep" dikategorikan berdasarkan makna konotatifnya, dan aspek spesifik dari setiap kata konotatif diidentifikasi. Setelah analisis, para peneliti memberikan penjelasan untuk data dan menarik kesimpulan berdasarkan temuan mereka. Hasilnya, 12 makna konotatif yang berbeda ditemukan dalam puisi ini. Sebagai kesimpulan, makna konotatif berbeda dari makna literal yang ditemukan dalam kamus, dan terkadang lebih sulit untuk menguraikan makna tersembunyi di baliknya.Kata Kunci: Puisi, Konotatif, Denotatif